IMPLEMENTASI PSIKOLOGI PENDIDIKAN MENUJU RESILIENSI AKADEMIK PADA MAHASISWA - Alma Yulianti; Mudjiran Mudjiran; Herman Nirwana (Psyche: Jurnal Psikologi, 2021)
Resilience is a personal quality that allows individuals to rise up when facing difficulties, especially for students who are undergoing their final semester in college. Various challenges and difficulties caused by thesis work are problems that cannot be avoided for every student. This study is focused on studying the role of academic resilience in final year students. The research subjects consisted of 7 undergraduate students from 19 to 24 years of age. Students are expected to have resilience in facing academic challenges called academic resilience. Academic resilience is defined as the ability of students to withstand difficult conditions, bounce back from adversity, overcome difficulties, and adapt positively to academic pressure and demands. Keywords: Implementation, Academic Resilience, Education